Strategies for ensuring sustainable democracy in South Africa - Hilliard, Victor G; Notshulwana, Mxolisi (University of the Free State, 2001)
Englsih: This article examines the South African experience of democracy and focuses in particular on the democratisation of South Africa’s government and administration. The democratisation process has not been problem-free. The tone was set by the negotiation of the 1993 Interim Constitution Act, and later the promulgation of a 1996 Constitution Act. Both these Constitution Acts made provision for a host of human rights and for a democratic dispensation intended to function in a multiparty context. To promote sustainable democracy, and to ensure that the majority of constitutional principles are upheld as far as possible, various checks and balances have to be built into the South African governmental system. It is essential that all public functionaries be accountable for their actions and/or lack thereof. This article examines some of the mechanisms or strategies to keep democracy vibrant and to ensure that public functionaries serve the general good, and do not pursue selfish, parochial interests.

Afrikaans: Hierdie artikel ondersoek hoe die demokrasie in Suid-Afrika ervaar word en fokus veral op die demokratisering van die Suid-Afrikaanse regering en administrasie. Die demokratiseringsproses was nie sonder haakplekke nie. Die onderhandeling van die interim Grondwet in 1993 en die promulgering van die Grondwet in 1996 was toonaangewend vir die demokratiseringsproses. Albei hierdie Grondwette het voorsiening gemaak vir ’n wye verskeidenheid menseregte en vir ’n demokratiese bestel wat in ’n veelpartyopset moet funksioneer. Om volhoubare demokrasie te bevorder en om te verseker dat die meerderheid van die grondwetlike beginsels sover moontlik gehandhaaf word, moet verskeie wigte en teenwigte in die Suid-Afrikaanse regeringstelsel ingebou word. Dit is noodsaaklik dat alle openbare funksionarisse verantwoordelik gehou moet word vir hulle optredes of die versuim daarvan. Hierdie artikel ondersoek sommige van die meganismes of sogenaamde strategieë om die demokrasie lewenskragtig te hou en om te verseker dat elke openbare funksionaris die algemene welsyn dien en nie selfbelang najaag nie.
Keywords: South Africa’s government; Democratisation process; Sustainable democracy